The last word - Birchall, Katy (St. Martin's Griffin, 2023)
"The Hating Game meets Beach Read in Katy Birchall's enemies-to-lovers romcom The Last Word, about a young journalist who puts her career (and her heart) on the line when her former work nemesis is hired in her newsroom. Harper Jenkins is at the top of her game. A brilliant, determined journalist with a well-known knack for getting tight-lipped Hollywood stars to open up to her, Harper loves her job as Celebrity Editor at a newspaper's glossy weekend magazine and has the best contacts in the business. But when her awful boss hires talented reporter Ryan to be the new Features Editor, Harper is furious. Because the two have met before: a decade ago, they were interns at the same publication, where they fell into a whirlwind romance...until Ryan betrayed Harper, and they never spoke again. Thrown together in a busy newsroom, their dynamic is a disaster from the start. They can't agree on anything and bicker constantly-Ryan can't bear how chaotic and messy Harper is; Harper finds Ryan's condescending nature infuriating. They clash over who's writing what article, and fight over who's going to which event. Yet as they're forced to spend more and more time together, Harper realizes she may have misjudged Ryan and can't help but feel a spark growing between them. Long buried feelings start to resurface and, when they're thrown together on a romantic press trip abroad, their chemistry comes to a head. But all is fair in love and magazines, and with the news that layoffs across the department are imminent, Harper is left to wonder: who will get the last word?"--